HUBUNGAN KONDISI LINGKUNGAN FISIK RUMAH DAN KEBERADAAN PEROKOK DALAM RUMAH DENGAN KEJADIAN PNEUMONIA PADA ANAK BALITA DI WILAYAH KERJA PUSKESMAS BALAPULANG KABUPATEN TEGAL - Imelsa Ika Wulandari; Suhartono Suhartono; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2016)
It was known for the last few years that the coverage of case finding of pneumonia in Indonesia and Central Java still under the national targets, including the national target in 2014 by 80%. Based on data from the Government of Central Java in 2014 about case finding of pneumonia in infants by sex, it was known that Tegal becomes the largest five for pneumonia cases in infants among other districts. One area of this district with high incidence of pneumonia is Public Health Center of Balupalang. This area has increased the number of pneumonia incidence for the last 3 years. This area also has the lowest number of healthy house in tegal district. This study was an analytic observasional study with case control design. The population of this study was all children under five years, that was located in Public Health Center of Balupalang in 2015. Number of samples were 43 respondents respectively in cases and controls, that was taken by purposive sampling. Data were collected by interviews and observations, then it was analyzed into univariate and bivariate analysis. the test of significance was using chi square and the magnitude of risk was counted using Odds Ratio. The results showed that three of ten independent variables were related with pneumonia incidence, i.e. level of humidity (p-value= 0.041; OR= 4.583), natural lighting intensity (p-value = 0.028; OR = 2.971) and large of ventilation (p-value = 0.045; OR = 2.777). This study concluded that there was relationship between the level of humidity, natural lighting intensity and large of ventilation with the incidence of pneumonia in infants.